Narrative Review of Factors Affecting Lower Back Pain among Workers in Pakistan - Ayesha Arooj; Aamir Aziz; Fariha Khalid; M. Hussain Iqbal (BioScientific Review, 2022)
According to the world health organization (WHO), lower back pain (LBP) is the most common healthhazard among workers and is among the top ten health hazards around the globe. The Global Burden ofDisease (GBD) 2010 stated LBP as amongst the top 6 diseases which cause disability injuries and otherchronic diseases. This is the impairment that poses the most economic burden on society as a whole,including individuals, businesses, and the government. This study aims to find out the factors that affectlower back pain among workers associated with different professions in Pakistan. Data were collectedfrom different databases, such as PubMed, Google scholar, and PEDro by using a predefined searchstrategy with proper Boolean terms ‘AND’ or ‘OR’ or ‘NOT’. The data were collected from theliterature available for past 10 years. Additionally, articles with relevant material and titles werereviewed for conducting the current research review. The most common risk factors that were seenalmost among all professions were static position and prolonged working hours, any work that demandsprolonged standing or sitting, bending or twisting, and improper lifting. Several professional workers areat high risk for developing LBP but among all the professions physiotherapists, sonographers, bankers,and shopkeepers were at higher verge for developing LBP. It was found that the prevalence of LBP isincreasing day by day and significantly affecting workers in every profession. Therefore, timelytrainings with proper ergonomic techniques could decrease LBP and increase economic productivity inPakistan. It can be said that good ergonomics for good economics.